A Three‐Dimensional Tetraphenylíethene‐Based Metal–Organic Framework for Selective Gas Separation and Luminescence Sensing of Metal Ions. Issue 27 (18th May 2016) - Yang, Wei; Chang, Ganggang; Wang, Hailong; Hu, Tong‐Liang; Yao, Zizhu; Alfooty, Khalid; Xiang, Shengchang; Chen, Banglin
Abstract : A three‐dimensional porous metal–organic framework (MOF), UTSA‐86, made up of cadmium ions and a chromophoric tetraphenylethene‐based tetracarboxylate ligand, 4′, 4′′′, 4′′′′′, 4′′′′′′′‐(ethene‐1, 1, 2, 2‐tetrayl)tetrakis(1, 1′‐biphenyl‐4‐carboxylic acid (H4 ettc), has been synthesized and characterized by single‐crystal X‐ray diffraction analysis. This multifunctional MOF exhibits permanent porosity, selective gas uptake, and luminescence sensing of metal ions. Abstract : A three‐dimensional multifunctional metal–organic framework (MOF), UTSA‐86, made up of cadmium ions and a tetraphenylethene‐based tetracarboxylate ligand has been synthesized and characterized by single‐crystal X‐ray diffraction analysis. This MOF exhibits permanent porosity, selective gas uptake, and luminescence sensing of metal ions.